Microflow Technology: Another Solution for the Site-Selective Modification of Multifunctionalized Molecules - Fuse, Shinichiro; Mifune, Yuto; Tanabe, Nobutake; Takahashi, Takashi (Synlett, 2014)
The synthesis of multifunctionalized organic molecules is challenging because multiple functional groups frequently causes unexpected side reactions. The recent emergence of microflow technology has offered a new solution to this problem. Herein, we wish to describe our recent achievements in the microflow synthesis of multifunctionalized molecules such as vitamin D and peptides.
Keywords: amides; peptides; vitamins; photochemistry; acylation